Systematics of the parasitoid wasp subfamily Banchinae (Hymenoptera; Ichneumonidae) in the Afrotropical region - Reynolds Berry, Terry (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.